EKSPLORASI ARSITEKTUR MADURA: DARI TANEAN LANJHANG KE BAHAN AJAR GEOMETRI DI SEKOLAH DASAR - Hariani, Shintia Shepti; Fijriyah, Izzah; Wardhani, Indah Setyo; Fadilah, Nur; Supriliyanti, Novi (Universitas Bhinneka PGRI, 2025)
The tanean lanjhang traditional house is a bridge between culture and geometry, as its structure is rich in geometric elements.its structure is rich in geometric elements. The aim of the research of this research is to explore architecture of tanean lanjhang, as a teaching material for geometry atgeometry teaching material in elementary school. Elementary School. This research uses qualitative research with researcher as a participant. Data collection techniques using observation, documentation, and literature study. Data analysis techniques include: reduction data reduction, data display, and verification. The research subjects were 2 tanean lanjhang houses in Bangkalan and Pamekasan. The results of this study concluded that in the tanean lanjhang traditional house, there are teaching materials teaching materials that can be used in mathematics learning materials. The implementation of this research can be applied in teaching materials, such as culture-based teaching materials, culture-based LKPD and culture-based assessments. and culture-based assessments.